(untitled) (American Journal of Islam and Society, 2006)
I begin my brief story in the 1960s, when many Uyghur (also spelled “Uygur” and “Uighur”) people, including myself, struggled against starvation. The already difficult lives of Uyghurs living in East Turkestan1 (also known as the Xinjiang Uyghur Autonomous Region [XUAR]) under Chinese government rule became much worse during the Cultural Revolution. Everything was rationed and controlled by the government and food was in very short supply. There was no private enterprise. Trying to find any way I could to alleviate the poverty we were suffering, I started to make and sell children’s clothes. I also took in laundry to earn some money. From there, I began to travel to different cities (first within East Turkestan and later throughout China) buying fabrics and garments and selling them on the street. Of course, this was not allowed under the communist system, and many times the Chinese police confiscated all of my goods and charged me with “taking the road of the capitalists.” Nor was it usual for a woman to travel in the region. I endured many hardships and indignities, but I was determined to care for my children and improve my life. During the 1980s, as China began its economic reforms, I was able to set up a small store to do business in Urumchi, the capital of East Turkestan, and gradually started to prosper. I always tried to encourage the other Uyghur street sellers and merchants as well. In March 1987, I established the “Eighth of March” market (named in honor of International Women’s Day), a covered marketplace that housed ninety-three stores and stands. In 1989, I built a seven-story apartment building, and a few years later I built the Rebiya Kadeer Department Store in downtown Urumchi. The Uyghur street vendors could come and sell their goods in my store. At some point in my struggle for economic independence, I became one of the ten richest people in China, for my business eventually grew into a multi-million dollar trading company ...